Development and characterization of an immortalized swine respiratory cell line for influenza A virus research - Neasham, Peter J.; Pliasas, Vasilis C.; North, J. Fletcher; Johnson, Celeste; Tompkins, S. Mark; Kyriakis, Constantinos S. (Frontiers in Veterinary Science, 2023)
Swine serve as an important intermediate host species for generating novel influenza A viruses (IAVs) with pandemic potential because of the host's susceptibility to IAVs of swine, human and avian origin. Primary respiratory cell lines are used in IAV research to model the host's upper respiratory tract in vitro. However, primary cell lines are limited by their passaging capacity and are time-consuming for use in industry and research pipelines. We were interested in developing and characterizing a biologically relevant immortalized swine respiratory cell line that could be used for efficient propagation and characterization of swine IAV isolates.Lung tissue for the generation of primary swine respiratory cells were isolated from the bronchi of an 8-week-old Yorkshire/Hampshire pig, which were immortalized by transduction of the SV40 T antigen using a lentivirus vector. The transduction of the SV40 T antigen was confirmed by Real Time RT-PCR in cells passaged greater than twenty times. Immortalized swine respiratory cells were shown to primarily express α2,6 sialic acid receptors. They were susceptible to both swine and human IAVs, swine viruses replicated to higher titers. In addition, we observed an increase in IL-6 and IL-1α protein secretion following infection with a swine H3N2 isolate, compared to infection with a seasonal human H3N2 virus. Following 20 passages, the immortalized cells retained the phenotype of the primary respiratory cells, while remained permissive to IAV infection without the addition of exogenous trypsin.Overall, we developed an alternative in vitro substrate that can contribute to the study of replication and transmission dynamics of IAVs in pigs, without the disadvantages, including low passage survivability and cost, of primary respiratory cells.